2016
DOI: 10.3892/ol.2016.4512
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status and protein expression of RASSF1A in endometriosis

Abstract: Abstract. Ras association domain family 1A (RASSF1A) gene inactivation by promoter hypermethylation is a common event in the development of a variety of types of human cancer. Accumulated evidence has demonstrated that DNA methylation serve a critical role in the pathogenesis of endometriosis. The aim of the present study was to analyze the methylation status and protein expression of RASSF1A in endometriosis (EMS). The ectopic and corresponding eutopic endometrium tissues were collected from 45 women with EMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The present study summarizes the genome-wide methylation profile of endometriosis. 17,20,21,27,30,33,39,44,46,47,51,54,[75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Many studies have reported abnormal methylation patterns of selected genes in endometriotic lesions and endometria of patients with endometriosis. We found peer-reviewed research articles published about the association of DNA methylation with endometriosis.…”
Section: Aberrant Methylation Patterns Of Selected Genes In Endometriosismentioning
confidence: 99%
“…The present study summarizes the genome-wide methylation profile of endometriosis. 17,20,21,27,30,33,39,44,46,47,51,54,[75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Many studies have reported abnormal methylation patterns of selected genes in endometriotic lesions and endometria of patients with endometriosis. We found peer-reviewed research articles published about the association of DNA methylation with endometriosis.…”
Section: Aberrant Methylation Patterns Of Selected Genes In Endometriosismentioning
confidence: 99%
“…Highly heterogeneous endometriotic lesions, which are removed during laparoscopic surgery, have been an attractive study object for both candidate gene-based and genome-wide DNA methylation studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Up to date, DNA methylation profiles of more than 10 candidate genes and transposable element involved in different pathways, such as hormonal signalling (PGR, ESR1, ESR2, COX-2, COMT), ovarian cancer progression (LINE-1), carcinogenesis (PAX2), tumour repressor and apoptosis-related genes (CDH1, RASSF), tissue remodelling (MMP2, MMP3, MMP7, TIMP3 and TIMP4) and genes needed for endometrial growth, differentiation, and implantation (HOXA10) have been investigated and associated with disease pathogenesis in whole endometriotic lesion biopsies (Table 1).…”
Section: High Tissue/cellular Heterogeneity -Dna Methylation Studies mentioning
confidence: 99%
“…The candidate gene-based and DNA microarray studies comparing endometria from women with and without endometriosis have brought out number of disease related genes (Table 2) [12,15,16,18,19,[33][34][35][36][37][38][39][40][41][42]. The candidate gene-based studies have reported dysregulation of genes involved in many important biological functions, such as hormonal regulation (COX-2), development of female genital tract (PAX2), endometrial growth and receptivity (HOXA10, HOXA11) and tumor suppression (RUNX3, RASSF1A, CDH1) [12,33,34,36,38,39,43,44].…”
Section: Modarate Tissue/cellular Heterogeneity -Dna Methylation Studmentioning
confidence: 99%